Measurement Properties of Instruments for Measuring of Lymphedema: Systematic Review. Issue 12 (1st December 2016) - Hidding, Janine T.; Viehoff, Peter B.; Beurskens, Carien H.G.; van Laarhoven, Hanneke W.M.; Nijhuis-van der Sanden, Maria W.G.; van der Wees, Philip J.
Abstract: Background: Lymphedema is a common complication of cancer treatment, resulting in swelling and subjective symptoms. Reliable and valid measurement of this side effect of medical treatment is important. Purpose: The purpose of this study was to provide best evidence regarding which measurement instruments are most appropriate in measuring lymphedema in its different stages. Data Sources: The PubMed and Web of Science databases were used, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Study Selection: Clinical studies on measurement instruments assessing lymphedema were reviewed using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) scoring instrument for quality assessment. Data Extraction: Data on reliability, concurrent validity, convergent validity, sensitivity, specificity, applicability, and costs were extracted. Data Synthesis: Pooled data showed good intrarater intraclass correlation coefficients (ICCs) (.89) for bioimpedance spectroscopy (BIS) in the lower extremities and high intrarater and interrater ICCs for water volumetry, tape measurement, and perometry (.98–.99) in the upper extremities. In the upper extremities, the standard error of measurement was 3.6% (σ=0.7%) for water volumetry, 5.6% (σ=2.1%) for perometry, and 6.6% (σ=2.6%) for tape measurement. Sensitivity of tape measurement in the upper extremities, using different cutoff points, varied from 0.73 to 0.90, and specificity values varied from 0.72 to 0.78. Limitations: No uniform definition of lymphedema was available, and a gold standard as a reference test was lacking. Items concerning risk of bias were study design, patient selection, description of lymphedema, blinding of test outcomes, and number of included participants. Conclusions: Measurement instruments with evidence for good reliability and validity were BIS, water volumetry, tape measurement, and perometry, where BIS can detect alterations in extracellular fluid in stage 1 lymphedema and the other measurement instruments can detect alterations in volume starting from stage 2. In research, water volumetry is indicated as a reference test for measuring lymphedema in the upper extremities.